Eksistensi Kebudayaan Merti Dusun dalam Kesenian Reog Manunggal Mudho Lestari Budoyo Kulonprogo - Dwi Oktaviani; Heri Kurnia (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
People's daily life is related to both pleasant and unpleasant phenomena. An example of a phenomenon that occurs is tradition. One of them is the Merti Hamlet tradition in Bonosoro Hamlet, Bumirejo Village, Lendah District, Kulonprogo Regency, Yogyakarta. This study aims to explore the Merti Dusun tradition, especially to increase community harmony and diversity. This research was conducted using the library research method with direct data collection or observation and gathering information by asking questions. The results of the study show that all Merti Dusun activities in Bonosoro Hamlet lead to a harmonious community through participation, cooperation and mutual cooperation regardless of differences in ethnicity, religion and social strata.